A critique of the evidence base for non-pharmacological sleep interventions for persons with dementia. (March 2013) - Brown, Cary A; Berry, Robyn; Tan, Maria C; Khoshia, Anjalee; Turlapati, Lakshmi; Swedlove, Fern
Disordered sleep in persons with dementia is a contributing factor for a range of health problems. The evidence base for non-pharmacological interventions has not been evaluated and clearly presented in the literature. This paper provides a structured Critical Literature Review of the evidence for non-pharmacological interventions to reduce disordered sleep in persons with dementia. The systematic search retrieved 29 studies that were evaluated for methodological quality. The quality of evidence ranged from conclusive for light therapy and activity to inconclusive for most other interventions. There is a paucity of conclusive research for non-pharmacological sleep interventions for persons with dementia. Most of the evidence about effective interventions is anecdotal and untested. There is a need for rigorous scientific inquiry, coupled with tacit knowledge to build a strong evidence base on non-pharmacological interventions for disordered sleep for persons with dementia.